REPORT OF THE WINTERING PARTY OF THE 9TH JAPANESE ANTARCTIC RESEARCH EXPEDITION 1968-1969 - Masayoshi MURAYAMA (Antarctic Record, 1969)
The National Antarctic Committee of the Science Council of Japan has decided to resume scientific research in the Antarctic by reopening Syowa. This base will serve as a permanent station for carrying out various kinds of observations and surveys of the East Antarctic Continent. The inland survey is for the purpose of studying continental ice, crustal structure, and geomagnetism following the geomagnetic meridian. During the period of February 11, 1968 to February 20, 1969 Syowa was manned by the 9th wintering party. The party consisted of the writer, who succeeded Dr. T. TORII as leader, plus 28 men including one correspondent of the press On account of the location of Syowa lying directly below the auroral zone, studies in the field of upper atmosphere physics have been conducted in continuation of last wintering party. We are limited in the scale of the station facility because of the transport capacity of the relief ship FUJI, but we were able to commence the study of cloud physics and medical science. The largest and highest ice continent in Antarctic lies to the south of Syowa. The distance between it and the South Pole is approximately 2,300 kilometers as the crow fhes While U. S. A. and U. S. S. R. have initiated an ambitious survey of the East Antarctic, the large portion of the continent remains unexplored A significant but hazardous scientific project remaining is the traverse between Syowa and the South Pole The Japanese expedition commenced the execution of this traverse. KD60, specially constructed snowmobile, was made available for the Pole trip Its special features include ability to withstand temperatures as low as minus 60 degrees Centigrade in the traverse over the ice plateau of the altitude of higher than 4,000 meters for a distance of 6,000 kilometers. The vehicle is equipped with a seismograph, an ice radar, a natural radio waves receiver, a gyrosyncompass for navigation, and radio transmitters and the like. It contains four berths plus kitchen and is capable of continuous operation fora five-month period. During the traverse the party conducted scientific observations and measurements of the following subjects : location, altitude, weather, topography, geology, ice thickness, geomagnetism, natural radio waves (VLF emission) and medical science. We left Syowa on Ongul Island on September 28, 1968 aboard four KD60's hauling fourteen sleighs which were loaded with 45 tons of fuel, food, and scientific apparatus. We proceeded southward along 43 degrees East Longitude. Forty days later we passed 76 degrees South Latitude. There-after we were plagued with softer-than-expected snow and an uneven snow cover caused by strong winds One of the KD60's had a trouble in the turbo-charger and we were forced to proceed onward without it. The equipments and stores of the abandoned vehicle were transferred onto the other vehicles and sleighs On the 46th day our train arrived at the U. S. Plateau Station which is located at 79 degrees 14 minutes South Latitude and 40 degrees 30 minutes East Longitude. There we received additional 10 tons of fuel Our journey thereafter proceeded more smoothly because of increasing sun radiation. On the 83rd day our party finally reached the U. S. Amundsen-Scott Station at the geographic South Pole A warm and most enthusiastic reception was held for us The route taken by the Japanese party was the longest of all ever attempted by any of Antarctic expeditions and covered a vast extension of virgin territory. On the Christmas Day, after attending to vehicle maintenance and fuel supply, our party headed back to Syowa. On our way to Plateau Station, we found our previous path uncovered and we were able to follow it easily. In the area north of 78 degrees South Latitude, however, the rut in the loose granular snow was generally filled with snow, but its outline was about 40% visible. Between 74 degrees and 72 degrees South Latitude our vehicles bumped and rolled because of hard sastrugi covering. Our journey ended on February 15, 1969 when we reached Syowa This traverse covered 5,182 kilometers in 141 days, averaging 36 kilometers per day The writer whishes to extend his most grateful acknowledgement to the cooperation and support given by the United States stations, and to the kindness rendered to us by the Australian, British, New Zealand and Soviet stations